Arabic Linguistic Approaches between the Reality of Origin and the Prospects for Development - Mazouz, Abd alhalim (Milev Journal of Research and Studies, 2021)
The Arabic linguistic lesson has developed greatly since the connection of Arab culture to modern linguistics in the Western world through scientific missions، as the process of authorship in this modern science was active in order to introduce it and its various schools and methods، and then this activity moved from the mere introduction of this science and the translation of western literature founded to look at Arabic based on linguistic data، in an effort to make the research in this language scientific. This consideration of language has tended to research the Arabic linguistic heritage through the linguistic heritage left by a group of ancient Arabic scholars - especially related to grammar - where Arab efforts have tried to reach the development of a new theory of Arabic grammar that corresponds to the Arabic language in its modern form and seeks to facilitate grammar، and emerged in this area several trends that were influenced in general by Western linguistic theories، as these efforts were classified in currents that look at the Arabic language in accordance with the principles built in this area. It's got those Western schools on it، the most important of these trends are: the structural descriptive trend، the rooting trend، the interpretive or obstetric trend، the functional trend and the synthesis trend. Through this article، we try to identify the reality of these Arabic linguistic approaches by diving into the circumstances of their origins، and then researching their theoretical origins and procedural principles in order to consider their ability to keep pace with developments in linguistic research and to anticipate their fate in the context of contemporary linguistic research.